2021
DOI: 10.24018/ejece.2021.5.1.294
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design, Dynamic Modeling and Analysis of a Hybrid Power System for a Catamarans Boat in Bangladesh

Abstract: Bangladesh is a land of rivers, canals, and lakes where water transportation is an essential means of transport. The country use boats as one of the leading resources of a carrier in its widespread inland waterways. Most of the currently used boats use only diesel for fuel. Appropriate use of renewable energy sources, particularly solar energy with diesel generators, could reduce diesel consumption. In this paper, a typical boat energy requirement was calculated to be 42.10 kWh/day. A boat could be driven by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Li= 20.94 μH (16) The grid side inductor Lg can be calculated as: Lg= 0.6 × Li (17) Lg= 16.766 μH (18) Finally, the filter capacitor (Cf) is designed in a way so that there should be a maximum 5% oscillation in the inverter output voltage for the stable operation of grid-tied PV system. The capacitance can be calculated using the below formulas as:…”
Section: Lcl Filter Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Li= 20.94 μH (16) The grid side inductor Lg can be calculated as: Lg= 0.6 × Li (17) Lg= 16.766 μH (18) Finally, the filter capacitor (Cf) is designed in a way so that there should be a maximum 5% oscillation in the inverter output voltage for the stable operation of grid-tied PV system. The capacitance can be calculated using the below formulas as:…”
Section: Lcl Filter Designmentioning
confidence: 99%
“…The results showed that the hybrid system is suitable for eliminating the subservience of rural areas on fossil fuels and providing power to remote areas. In [16], the author designed and simulated a PV system for a boat carrying 20 passengers in Bangladesh. From HOMER sizing results, 10.6 kW PV system is required.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed methodology has not been implemented in the real time. Mehedi et al [11] introduced a solar boat that includes PV of 10.6kw, DC gas generator of 1.6kw, and battery bank of 333Ah.The catamarans type passenger boat (CPB) is made of fiberglass polyester material, 12m in length and 4.8 m in width and the carrying capacity of catamaran boat is 20 passengers in a day. For the dynamic analysis and modelling author used MATLAB and HOMER PRO has been used.…”
Section: Overview Of Solar-powered Boatmentioning
confidence: 99%